Flattening and Unflattening: Philosophical Reflections on Images in Scientific Comics - Meer, Julia (Alternative francophone, 2022)
In my article, I undertake basic research on comics and knowledge transfer by comparing scientific comics with other forms of visualization in (the history of) science. In doing so, I elaborate the central characteristics of comics in reference to current research, and relate them to philosophical theories of images by arguing that the specific materiality of the images in general, and in comics in particular, has received little attention so far. The central thesis is that materiality is decisive for images not only to illustrate scientific theories but to become knowledge-generating media themselves.